What makes work meaningful and why economists should care about it - Milena Nikolova; Femke Cnossen (Global Labor Organization (GLO), 2020)
We demonstrate why meaningful work, i.e. job-related activities that individuals view as purposeful and worthwhile, matters to labour economists. Building on self-determination theory, which specifies the roles of autonomy, competence, and relatedness as preconditions for motivation, we are the first to explore the determinants of work meaningfulness. Specifically, using three waves of the European Working Conditions Survey, we show that autonomy, competence, and relatedness explain about 60 percent of the variation in work meaningfulness perceptions. Meanwhile, extrinsic factors, such as income, benefits, and performance pay, are relatively unimportant. Meaningful work also predicts absenteeism, skills training, and retirement intentions, which highlights the concept's economic significance. We provide new insights that could help organise the future of work in a meaningful and dignifying way and propose concrete avenues for future research on meaningful work in economics.
Keywords: J01; J30; J32; J81; I30; I31; M50; 330; meaningful work; motivation; non-monetary benefits of work; labour economics; labour market outcomes; self-determination theory